2020
DOI: 10.3389/fonc.2020.01248
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Nephron Sparing Surgery and Radical Nephrectomy in the Management of Unilateral Wilms Tumor: A Meta-Analysis

Abstract: Background: Unilateral Wilms tumor is the most common renal malignancy in the pediatric population. Although the onset of surgical intervention like radical nephrectomy has substantially reduced the mortality rate, recent evidence has raised concerns regarding several postoperative complications associated with this procedure. Nephron sparing surgery has been reported to avoid such postoperative complications and have high technical success rate. However, no attempt to date has been made to synthesize the evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…COG suggests that only the initiation of the treatment with surgery allows precise assessment of the local advancement stage and the histopathological type of the tumor, which is crucial for the selection of the type and intensity of postoperative treatment. The treatment results in both groups are comparable [18].…”
Section: Treatmentmentioning
confidence: 78%
“…COG suggests that only the initiation of the treatment with surgery allows precise assessment of the local advancement stage and the histopathological type of the tumor, which is crucial for the selection of the type and intensity of postoperative treatment. The treatment results in both groups are comparable [18].…”
Section: Treatmentmentioning
confidence: 78%
“…As of date, some excellent systematic reviews[ 40 41 ] and meta-analysis[ 42 ] on the topic of NSS in uWT are available. The first and only (RCT) study hitherto on the topic has been recently reported by a team of urologists from Belgaum, Karnataka, India.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al . [ 42 ] in a recent meta-analysis recommended the use of NSS for uWT. The procedure accounted for higher survivability and postoperative renal function and lesser incidence of relapse as compared to RN.…”
Section: Discussionmentioning
confidence: 99%
“…The self-rating anxiety scale (SAS) ( 12 ) and the self-rating depression scale (SDS) ( 13 ) were used to assess the psychological state before and after nursing, which included 20 items, with a total score of 80 points. The higher the total score is, the worse the psychological state of the children is.…”
Section: Methodsmentioning
confidence: 99%